Innovation and performance among firms in Finland: the impact of firm-level characteristics. (2nd September 2020) - Littunen, Hannu; Huovinen, Jari
The purpose of this paper is to analyse the role of firm-level characteristics together with the performance of small and medium enterprises (SMEs) associated with the introduction of different types of innovation (product/process/market/organisational). The paper is based on data from 830 firms located in Finland, and describes the development of a model for testing the firm-level factors that increase the innovativeness of SMEs. Logistic regression analysis was conducted to determine associations between innovativeness and the different explanatory factors put forward. The results show that the creation of novel product and process innovation appears to be associated with manufacturing industry, but on the other hand the creation of market innovation is linked to the field of trade. Furthermore, we found that the creation of process innovation was related to the location of firms, and innovation activity appears to be more common in rural areas than in central regions. The results also show that the creation of product/process/market/organisational innovation is positively associated with a firm's growth.